Compliance or reward? Here is the question - Ayvar Ayvar, Ricardo (2020)
Indecopi, through the Commission for the Defense of Free Competition, takes several measures to ensure that economic agents comply with the provisions of the Single Ordered Text of the Law for the Repression of Anti-Competitive Behavior. Among its most relevant functions over the last years, the detection of cartels, one of the most harmful anticompetitive conducts for the market, stands out. Through this type of practice, competitors agree to set prices, limit production, divide up customers, suppliers or geographical areas, and establish positions or abstentions in a given bidding process or public tender.In this article, the authors present the coexistence of the Compliance Programs and the Rewards Program as tools for detecting anti-competitive behavior, analyzing the criteria to be considered by individuals when choosing one of them. In that sense, some proposals will be made to improve the implementation of both programs from the above-mentioned disjunctive.